O impacto das redes e do ambiente institucional no processo de internacionalização dos periódicos científicos - Encarnação, Jackeline Ferreira da (2014)
This study aims to describe and understand the institutional environment and networks influence the internationalization of scientific journals. The assumption defended in this dissertation is that a magazine which has strong presence in the network in conjunction with a high perception of pressure from the institutional environment is more prone to internationalize magazine. The theoretical foundation is grounded in network theory, and institutionalism. Through a qualitative research methodology, pick up will understand what is the insertion of the magazine on the network and what is the understanding that the publisher has on the institutional environment and how this understanding leads to the internationalization process. It is perceived as a result of the low set in the context of networks, except those magazines that has already started its internationalization process, regarding institutional environment, it was noted how high the perception of publishers, regardless of the stage of internationalization of the journal.